AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence

Rapport de l’échange de connaissances - Koomar, Saalim; Rasolohery, Hasiniavo; Oojorah, Avinash; Udhin, Waaiza (EdTech Hub, 2025)
This is a report on a knowledge exchange visit between the Ministry of National Education of Madagascar and the Mauritius Institute for Education. The visit focused on sharing lessons and discussing ongoing projects related to technology in education. Key objectives included presenting successes and challenges of distance learning, discussing pedagogical design and digital platforms, and exploring long-term collaboration. School visits provided insights into technology integration in classrooms and teacher experiences. The report details the workshop's activities, participants, and key points, emphasising the importance of data-driven projects, feedback mechanisms, and continuous evaluation. Recommendations for future collaboration include short-term actions like remote communication and training, medium-term initiatives like co-presenting at conferences and personnel exchange, and long-term goals like co-applying for regional research projects. Keywords: teacher professional development; Madagascar; Moodle; knowledge exchange; EdTech; pedagogy Ce rapport porte sur une visite d’échange de connaissances entre le Ministère de l’Éducation Nationale de Madagascar et le Mauritius Institute for Education. La visite avait pour objectif de partager les enseignements tirés et de discuter des projets en cours liés aux technologies éducatives. Les principaux objectifs comprenaient la présentation des succès et des défis de l’apprentissage à distance, la discussion sur la conception pédagogique et les plateformes numériques, ainsi que l’exploration d’une collaboration à long terme. Les visites d’écoles ont permis d’observer l’intégration des technologies en classe et l’expérience des enseignants. Le rapport détaille les activités de l’atelier, les participants et les points clés, en mettant l’accent sur l’importance des projets basés sur les données, des mécanismes de retour d’information et de l’évaluation continue. Les recommandations pour une future collaboration incluent : Actions à court terme : communication et formation à distance; Initiatives à moyen terme : co-présentation lors de conférences et échanges de personnel; Objectifs à long terme : candidature conjointe à des projets de recherche régionaux. Mots clés: formation pédagogique; Madagascar; Moodle; échange de connaissances; technologie dans l’éducation; pédagogie An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Guide pour les utilisateurs de la tablette et de la plateforme Formation À Distance - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a practical guide for users of a tablet for the distance learning platform (FAD), specifically for 2000 primary teachers in Madagascar. It covers: Tablet Basics: How to use the tablet, buttons, screen, touch controls, navigation, and settings. Accessories: Information on the solar charger / power bank and mini-speaker. Communication: Instructions on making calls, sending SMS and emails, and accessing the internet. Applications: Guides for using applications for training content and exercises. Online Platform: Instructions for accessing and using the Moodle online platform for assessments and resources. Tablet Care: Tips for protecting the tablet and optimizing battery life. The guide is intended for beginners and provides step-by-step instructions with illustrations. It also includes a list of abbreviations and acronyms. Keywords: teacher professional development; Madagascar; Moodle; tablet; user guide Ceci est un guide pratique destiné aux utilisateurs d’une tablette pour la plateforme d’apprentissage à distance (FAD), spécifiquement conçu pour 2000 enseignants du primaire à Madagascar. Il couvre : Bases de la tablette : Utilisation de la tablette, boutons, écran, commandes tactiles, navigation et paramètres. Accessoires : Informations sur le chargeur solaire/batterie externe et le mini-haut-parleur. Communication : Instructions pour passer des appels, envoyer des SMS et des e-mails, et accéder à Internet. Applications : Guides d’utilisation des applications pour les contenus de formation et les exercices. Plateforme en ligne : Instructions pour accéder et utiliser la plateforme Moodle pour les évaluations et les ressources. Entretien de la tablette : Conseils pour protéger la tablette et optimiser l’autonomie de la batterie. Ce guide est destiné aux débutants et propose des instructions pas à pas avec illustrations. Il comprend également une liste d’abréviations et d’acronymes. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les utilisateurs An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing BETA - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a report on the Beta testing of a digital learning platform and applications developed for the Ministry of Education in Madagascar. The project aims to train 16,000 teachers, with 2,000 utilising distance learning via tablets. The Beta user testing focused on the pedagogical relevance, usability, and ergonomics of the platform and two offline applications. Twenty-one teachers participated, evaluating tasks like launching applications, navigating content, accessing multimedia, and completing exercises / evaluations. Results showed significant improvement from the Alpha user testing, with high success rates for accessing and navigating modules. However, over 50% of users still found the platform difficult to use, particularly for login, navigation, and profile modification. The applications were generally functional but needed adjustments to content presentation and visual quality. Recommendations included simplifying the platform's interfaces, enhancing user guides, and addressing specific content issues. The document emphasises the importance of ongoing quality assurance and an iterative approach to refining the platform. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce rapport porte sur le test Beta d’une plateforme d’apprentissage numérique et des applications développées pour le Ministère de l’Éducation à Madagascar. Le projet vise à former 16 000 enseignants, dont 2 000 via l’apprentissage à distance sur tablette. Les tests utilisateurs en phase Beta ont évalué la pertinence pédagogique, l’ergonomie et la convivialité de la plateforme ainsi que de deux applications hors ligne. Vingt et un enseignants ont participé, réalisant des tâches telles que le lancement des applications, la navigation dans les contenus, l’accès aux éléments multimédias et la réalisation d’exercices/évaluations. Les résultats montrent une amélioration significative par rapport aux tests Alpha, avec des taux de réussite élevés pour l’accès et la navigation dans les modules. Cependant, plus de 50 % des utilisateurs ont encore rencontré des difficultés, notamment pour la connexion, la navigation et la modification du profil. Les applications étaient globalement fonctionnelles, mais nécessitaient des ajustements dans la présentation des contenus et la qualité visuelle. Les recommandations incluent la simplification des interfaces de la plateforme, l’amélioration des guides utilisateurs et la correction de problèmes spécifiques liés aux contenus. Le document souligne l’importance de l’assurance qualité continue et d’une approche itérative pour affiner la plateforme. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

From algorithm outputs to classroom impact: A conversation with Marian Abu, director of teacher management at the Teaching Service Commission - Frazer, Madleen Madina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Timor-Leste - A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Summary: EdTech in Cambodia - A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Cambodia. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
Keywords: HLR3; _r:AddedByZotZen

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)